Nonlinear periodic systems with unilateral constraints - Aizicovici, Sergiu (2020)
We consider a general periodic system driven by a nonlinear, nonhomogeneous differential operator, with a maximal monotone term which is not defined everywhere. Using a topological approach based on Leray-Schauder alternative principle, we show the existence of a periodic solution.